Alloplastic Facial Implants - Hsieh, Tsung-yen; Dhir, Karan; Binder, William J.; Hilger, Peter Andrew (Facial Plastic Surgery, 2021)
As the face ages, there is thinning of the epidermis, volume loss and rearrangement of the soft tissues, and malabsorption of the skeletal framework. It is essential to have a thorough understanding of the aging process for successful facial augmentation and rejuvenation. Alloplastic implants can be used to provide a long-lasting solution for augmentation of skeletal deficiencies, restoration of facial irregularities, and rejuvenation of the face. In this study, we describe the ideal implant characteristics along with the advantages and disadvantages of various implant materials. We also present techniques in nasal and premaxillary augmentation, midface augmentation, mandibular augmentation, and lip augmentation. Additionally, computer-aided design and manufacturing as well as bioprinting are emerging technologies with growing applications in facial plastic and reconstructive surgery. We discuss their role in the creation of patient-specific custom implants. The overall goal of facial rejuvenation is to address multiple aspects of the facial aging process including deficiencies in the skin, soft tissues, and skeletal framework. The use of alloplastic implants alone or synergistically with additional surgical procedures can restore a wide range of anatomical deficits that occur with age.
Keywords: alloplastic implant; facial implant; mandibular augmentation; chin augmentation; cheekbones; CAD-CAM